Diffusion MRI in peripheral nerves: optimized b values and the role of non-Gaussian diffusion - Fösleitner, Olivia; Sulaj, Alba; Sturm, Volker Jörg Friedrich; Kronlage, Moritz; Godel, Tim; Preisner, Fabian; Nawroth, Peter Paul; Bendszus, Martin; Heiland, Sabine; Schwarz, Daniel (Radiology, 2022)
Background - - Diffusion-weighted imaging (DWI) provides specific in vivo information about tissue microstructure, which is increasingly recognized for various applications outside the central nervous system. However, standard sequence parameters are commonly adopted from optimized central nervous system protocols, thus potentially neglecting differences in tissue-specific diffusional behavior. - - Purpose - - To characterize the optimal tissue-specific diffusion imaging weighting scheme over the b domain in peripheral nerves under physiologic and pathologic conditions. - - Materials and Methods - - In this prospective cross-sectional study, 3-T MR neurography of the sciatic nerve was performed in healthy volunteers (n = 16) and participants with type 2 diabetes (n = 12). For DWI, 16 b values in the range of 0-1500 sec/mm2 were acquired in axial and radial diffusion directions of the nerve. With a region of interest-based approach, diffusion-weighted signal behavior as a function of b was estimated using standard monoexponential, biexponential, and kurtosis fitting. Goodness of fit was assessed to determine the optimal b value for two-point DWI/diffusion tensor imaging (DTI). - - Results - - Non-Gaussian diffusional behavior was observed beyond b values of 600 sec/mm2 in the axial and 800 sec/mm2 in the radial diffusion direction in both participants with diabetes and healthy volunteers. Accordingly, the biexponential and kurtosis models achieved a better curve fit compared with the standard monoexponential model (Akaike information criterion >99.9% in all models), but the kurtosis model was preferred in the majority of cases. Significant differences between healthy volunteers and participants with diabetes were found in the kurtosis-derived parameters Dk and K. The results suggest an upper bound b value of approximately 700 sec/mm2 for optimal standard DWI/DTI in peripheral nerve applications. - - Conclusion - - In MR neurography, an ideal standard diffusion-weighted imaging/diffusion tensor imaging protocol with b = 700 sec/mm2 is suggested. This is substantially lower than in the central nervous system due to early-occurring non-Gaussian diffusion behavior and emphasizes the need for tissue-specific b value optimization. Including higher b values, kurtosis-derived parameters may represent promising novel imaging markers of peripheral nerve disease. - - ©RSNA, 2021 - - Online supplemental material is available for this article. - - See also the editorial by Jang and Du in this issue.
Published online: Oct 19 2021
Gesehen am 12.04.2022